2017
DOI: 10.7748/ncyp.2017.e966
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neonate adhesive skin injuries in a Jordanian intensive care unit

Abstract: Adhesive skin injuries were found in more than one quarter of the neonates in this NICU and healthcare service providers should endeavour to minimise the occurrence of these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…The respondents reported that in their clinical practice, skin complications surrounding PIVC sites occurred rarely or sometimes. This is in contrast to studies which highlight that vascular access devices are among the most common device related to neonatal pressure and adhesive injuries (August et al, 2017;Habiballah, 2017;Liversedge et al, 2018;Nist et al, 2016;Sweeney et al, 2018). It may also reflect a lack of understanding of skin injuries and reactions that seem innocuous such as redness and adhesive related injuries.…”
Section: Discussionmentioning
confidence: 90%
“…The respondents reported that in their clinical practice, skin complications surrounding PIVC sites occurred rarely or sometimes. This is in contrast to studies which highlight that vascular access devices are among the most common device related to neonatal pressure and adhesive injuries (August et al, 2017;Habiballah, 2017;Liversedge et al, 2018;Nist et al, 2016;Sweeney et al, 2018). It may also reflect a lack of understanding of skin injuries and reactions that seem innocuous such as redness and adhesive related injuries.…”
Section: Discussionmentioning
confidence: 90%
“…The excoriation was the most frequent skin lesion in our study, and this was caused by medical adhesives used to fix devices (plaster and microporous tape) to protect the skin (microporous adhesive tape and hydrocolloid plate) and electrodes for cardiac monitoring. Similarly, a study from university hospital in Jordan discovered that lesions were also caused by fixing medical devices to the skin (Habiballah, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal population, these limitations are particularly apparent and produce several unique adverse outcomes. The frequency of false alarms secondary to the frequent movement of newborns is associated with provider alarm fatigue, infant hearing loss, and a disruptive environment for development [ 8 , 9 , 10 , 11 , 12 ]. Additionally, the humid environment of neonatal incubators and the infant’s thin, underdeveloped skin cause the adhesive in electric leads to fail and require frequent changing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the humid environment of neonatal incubators and the infant’s thin, underdeveloped skin cause the adhesive in electric leads to fail and require frequent changing. The recurrent application of adhesive to the fragile premature skin causes breakdown and inflammation of their dermal barrier, introducing possible sources for infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%